1985
DOI: 10.1002/bjs.1800721209
|View full text |Cite
|
Sign up to set email alerts
|

Pre- versus postoperative radiotherapy in rectal carcinoma: an interim report from a randomized multicentre trial

Abstract: Since October 1980 a randomized multicentre trial has been in progress among patients with rectal carcinoma, in whom high-dose fractionated pre-operative irradiation (total dose 25.5 Gy in 5-7 days) is being tested against postoperative irradiation to a high dose level using a conventional fractionation scheme (totally 60 Gy in 8 weeks) delivered only to a high-risk group of patients (Dukes' stages B and C). The primary aim of the trial is to investigate whether local recurrence rate differs between the two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
6

Year Published

1989
1989
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(52 citation statements)
references
References 29 publications
3
43
0
6
Order By: Relevance
“…Between 12-27% of the patients did not receive the planned postoperative dose (26,(28)(29)(30), whereas this occurred in less than 10% in the groups of patients randomized to preoperative radiotherapy (19)(20)(21)(22)(23)(24)(25). This difference in acute toxicity was seen also in the trial contrasting a preoperative approach to a postoperative one (37).…”
Section: Acutelsubacute Toxicitymentioning
confidence: 79%
See 3 more Smart Citations
“…Between 12-27% of the patients did not receive the planned postoperative dose (26,(28)(29)(30), whereas this occurred in less than 10% in the groups of patients randomized to preoperative radiotherapy (19)(20)(21)(22)(23)(24)(25). This difference in acute toxicity was seen also in the trial contrasting a preoperative approach to a postoperative one (37).…”
Section: Acutelsubacute Toxicitymentioning
confidence: 79%
“…The extent of this problem is not possible to evaluate in postoperative trials since only those with an uneventful postoperative period and in shape for randomization within the stipulated time period, e.g., 4-6 weeks, will be included. The only trial that can evaluate how often patients are not in shape for initiating the postoperative radiotherapy within a certain time period is the Uppsala trial (37) in which patients were randomized prior to surgery. It was then found that the radiotherapy could be started within 6 weeks in only 54% of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table 1, which displays all controlled, randomized trials, when the same dose was used, the effect on the local recurrence rate was far better with preoperative radiotherapy than with postoperative radiotherapy. The question of timing -pre-or postoperative therapy -has been addressed in only one randomized trial in which patients were allocated to preoperative or postoperative radiotherapy (29,30). In that trial, the Uppsala trial, preoperative radiotherapy was superior to postoperative irradiation in reducing local recurrence rates.…”
Section: Adjuvant Treatmentmentioning
confidence: 99%